HPV16-associated tumors control myeloid cell homeostasis in lymphoid organs, generating a suppressor environment for T cells - Stone, Simone Cardozo; Marques Rossetti, Renata Ariza; Bolpetti, Aline [UNESP]; Boccardo, Enrique; Araujo Souza, Patricia Savio de; Lepique, Ana Paula (Federation Amer Soc Exp Biol, 2014)
Tumors are complex structures containing different types of cells and molecules. The importance of the tumor microenvironment in tumor progression, growth, and maintenance is well-established. However, tumor effects are not restricted to the tumor microenvironment. Molecules secreted by, as well as cells that migrate from tumors, may circulate and reach other tissues. This may cause a series of systemic effects, including modulation of immune responses, and in some cases, leukocytosis and metastasis promotion. Leukocytosis has been described as a poor prognostic factor in patients with cervical cancer. The main etiological factor for cervical cancer development is persistent infection with high oncogenic risk HPV. Our laboratory has been exploring the effects of high oncogenic risk, HPV-associated tumors on lymphoid organs of the host. In the present study, we observed an increase in myeloid cell proliferation and alteration in cell signaling in APCs in the spleen of tumor-bearing mice. In parallel, we characterized the cytokines secreted in the inflammatory and tumor cell compartments in the tumor microenvironment and in the spleen of tumor-bearing mice. We show evidence of constitutive activation of the IL-6/STAT3 signaling pathway in the tumor, including TAMs, and in APCs in the spleen. We also observed that IL-10 is a central molecule in the tolerance toward tumor antigens through control of NF-B activation, costimulatory molecule expression, and T cell proliferation. These systemic effects over myeloid cells are robust and likely an important problem to be addressed when considering strategies to improve anti-tumor T cell responses.
Keywords: Human papillomavirus; Cytokines; Systemic effects; Immune evasion; Cell signaling